INTEGRASI PEMBELEJARAN STEAM DAN COMPUTATIONAL THINKING BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN PEMAHAMAN MATERI GAYA GESEK PADA SISWA KELAS IV SDN UTERAN 01 - Pinta Styaning Pambudi; Vivi Rulviana; Aning Triastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Classroom action research generally aims to improve the quality of learning for class IV students at SDN Uteran 01. In particular, it aims to: (1) Describe the implementation of integrated STEAM and Computational Thinking style learning based on local wisdom; and (2) Knowing the extent of understanding of the concept of integrated friction force in STEAM and Computational Thinking based on local wisdom. The research was carried out in two cycles, where each cycle consisted of planning, implementation, observation and reflection stages. Cycle I consists of two meetings, as does Cycle II. The data analysis techniques used are descriptive and comparative. Student activity data is explored using the Student Activity Observation Sheet, while data on student learning outcomes is explored using concept understanding tests. The results of the research showed that: (1) The average percentage of students' conceptual understanding of friction material at the pre-cycle stage was 30% (less understanding); (2) The average percentage of students' conceptual understanding of friction material increased by 65% (misconceptions) after implementing the integration of STEAM and CT based on local wisdom (gasing); and (3) After carrying out reflection in cycle I, cycle II was carried out with the result that the average percentage of students' concept understanding increased by 85% (concept understanding).